Investigation of the Trivalent Chromium Process Conversion Coating as a Sealant for Anodized AA2024-T3. Issue 11 (28th July 2020) - Shruthi, T. K.; Walton, Jack; McFall-Boegeman, Sarah; Westre, Sjon; Swain, Greg M.
Abstract : The sealing of an anodic coating on AA2024-T3 with a trivalent chromium process coating (TCP-HF) was investigated. Specimens were anodized in 9.8 wt% H2 SO4 at 15 V DC (23 min) producing an oxide coating weight of ca. 1200 mg ft −2 and a thickness of ca. 5 μ m. Elemental analysis revealed the sealant forms across the outer oxide layer and within the pores up to a depth at least approaching 1 μ m. Anodic and cathodic currents in potentiodynamic polarization curves were suppressed by 5–10× and low frequency impedance (Z0.01 Hz ) values were 5× higher for anodized specimens sealed with TCP (∼5 × 10 6 ohm-cm 2 ), as compared to the unsealed anodized controls. During continuous exposure to 3.5 wt% NaCl, Z0.01 Hz values remained unchanged and greater than 10 6 ohm-cm 2 after 5 days for the TCP-sealed specimen and decreased by 10× for the unsealed anodized control after just three days. A 14-day (336 h) neutral salt-spray exposure produced no significant pitting, discoloration or major coating detachment on anodized specimens sealed with TCP. Overall, the results indicate that the TCP sealant increases the barrier properties of the anodic coating and functions to provide anodic and cathodic corrosion protection.